Origins : fourteen billion years of cosmic evolution - Tyson, Neil deGrasse; Goldsmith, Donald (New York : W.W. Norton & Company, 2014)
Drawing on the current cross-pollination of geology, biology and astrophysics, Origins brings to life the thrilling astronomical discoveries of recent years.
Originally published: 2005.
Includes bibliographical references (pages 323-325) and index.
CSE
Trim Education
Keywords: Cosmology; Evolution; Cosmology -- Popular works; Computer science